WEB-Based Village Application at Singabangsa’s Village Head Office - Andri Cahyo Purnomo; Hardikan Arief Nugraha Sofyan; Febian Hendra Saputra (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
The Application of Information Technology currently has been spread almost in all areas of administrative management is no exception At the head office of the village. However, the information and data archiving service of the resident at the Singabangsa Village Head Office which is still manual, resulted in the ineffectiveness of information can be submitted to the community and the slow pace of population data collection. Public Information needs and The enormous population growth makes the researcher aim to design a village information system that can deliver efficient and accurate population data and easy in updating data. To overcome the above problems it is necessary an automation system capable of providing village information services and population data which are classified according to category until can be calculated statistically quickly, accurately and efficiently. The purpose of this village information system to optimize information services by providing village information and population that can be accessed easily with precise and accurate. In this research the researcher applies research method in the form of observation method, interview, study literature, SWOT analysis, system analysis and system design. This system is designed by using PHP programming language as well as MySQL database. Benefits and advantages in the use of village-based information system (SID) is the process of information services can be done easily and search data demographics more accurate and faster. The final result of this research is a web village information system design (SID).